An Observational Study of 2, 248 Patients Presenting With Headache, Suggestive of Subarachnoid Hemorrhage, Who Received Lumbar Punctures Following Normal Computed Tomography of the Head. (19th October 2015) - Sayer, David; Bloom, Ben; Fernando, Katalin; Jones, Stuart; Benton, Sally; Dev, Shumontha; Deverapalli, Sathish; Harris, Tim
Abstract: Objectives: The objective was to determine the incidence of subarachnoid hemorrhage (SAH) diagnosed by lumbar puncture (LP) when the head computed tomography (CT) was reported as demonstrating no subarachnoid blood. Methods: Data were obtained on patients who received LP to diagnose or exclude SAH attending six hospitals over 5 years. Subsequent investigations and outcomes were reviewed in all patients with LPs that did not exclude SAH. Results: A total of 2, 248 patients were included. A total of 1, 898 LPs were suitable for biochemical analysis, of which 92 (4.8%) were positive for blood, suggesting SAH; 1, 507 (79.4%) were negative; and 299 (15.6%) were inconclusive. Of the 92 patients with positive cerebrospinal fluid analysis, eight patients (0.4%) had aneurysms on further imaging, and one had a carotid cavernous fistula. Conclusions: In patients presenting to the emergency department with acute severe headache, LP to diagnose or exclude SAH after negative head CT has a very low diagnostic yield, due to low prevalence of the disease and uninterpretable or inconclusive samples. A clinical decision rule may improve diagnostic yield by selecting patients requiring further evaluation with LP following nondiagnostic or normal noncontrast CT brain imaging.